A Qualitative Study of Teamwork Among Care Providers in the Implementation of Interprofessional Collaboration in Hospitals - Delima, Mera; Boti, Tanti; Dioso, Regidor III; Devitra, Anferi (Universitas Fort De Kock Bukittinggi, 2025)
Background: Interprofessional collaboration is a key element in providing high-quality patient care. Interprofessional Collaboration (IPC) practice is a form of collaborative cooperation between health workers to ensure optimal patient care. Professional Care Providers (PCP) with different professional backgrounds are required to contribute individually and in teams. This study aims to determine the description of team collaboration practices between PCP in implementing Interprofessional Collaboration at the Hospital. Methods: This study used a qualitative design with a phenomenological approach to explore interprofessional collaboration practices at the Hospital. Data collection was carried out through in-depth interviews and Focus Group Discussions. The collected data were recorded, transcribed, and analyzed using thematic analysis. The research informants numbered 12 people, consisting of 3 hospital services in charge of doctors, 3 nurses, 3 pharmacists, and 3 dieticians. The study took place in October–November 2024. Results: The result of the study showed that interprofessional collaboration at the Hospital had not been running optimally. Joint visit activities involving the four professions were very rare. The number of pharmacists and dietitians who should support collaboration were not sufficient in quantity. The clinical competence of nurses in supporting collaboration was still not fulfilled. Most PCP did not understand the concept of IPC well, the dominance of collaboration tended to occur among doctors and nurses, while other professions were less involved. Factors that hinder the optimization of IPC include a lack of understanding of the concept of collaboration, the small number of certain health workers such as pharmacists and dietitians, and the lack of special training related to IPC. Conclusion: Hospitals need to make efforts to improve understanding and implementation of interprofessional collaboration through education, training, and strengthening policies that support IPC practices. Socialization of regulations and implementation of Interprofessional Collaboration needs to be carried out periodically so that PCP understands the concept of IPC well. Routine evaluation is also important to ensure the effectiveness and sustainability of interprofessional collaboration in health services